Nasal Cytology: A Comparative Study of Two Different Techniques of Processing—Smeared versus Cytocentrifuged Slides. (14th November 2018) - Bartoli, Maria Laura; Cristofani-Mencacci, Lodovica; Scarano, Mariella; Nacci, Andrea; Latorre, Manuela; Bacci, Elena; Paggiaro, Pierluigi; Seccia, Veronica
Abstract : Nasal cytology is a precious tool to study nasal disorders, but in current literature, there is no consensus on the standardization of the processing procedure of the obtained samples. Therefore, we decided to test on specimens obtained by nasal scraping, a common way of nasal specimen sampling, two different processing techniques, smear and cytocentrifugation, and compare them in terms of inflammatory cell content, quality of slides, and validity on clinical assessment. We analyzed 105 patients with suspected sinonasal diseases, and in each patient, we performed nasal cytology with both techniques. Our analysis showed a good correlation between the two techniques for neutrophil and eosinophil percentages, both returned well-preserved cells, and showed higher neutrophil percentage in males and in smokers and higher eosinophil percentage in patients with polyposis, with a good concordance with clinical symptoms, as measured by a specific disease-related questionnaire (Sino-Nasal Outcome Test-22). Technically speaking, smeared slides were easier to prepare, with no need of dedicated equipment, but cell distribution was better in cytocentrifuged slides allowing shorter reading time. In conclusion, both techniques can be considered superimposable and worthy to be used.